Decadal variation of the summer extreme high temperature days in northern Eurasia during 1960–2018 - Fan, Yi; Yao, Xiaona; Zhou, Botao; Li, Huixin; Liu, Mei (Frontiers in Earth Science, 2023)
Unprecedented heat waves have been demonstrated sweeping across much of the Northern Hemisphere in recent summers. However, this study reveals that for northern Eurasia (30°–70°N, 10°–130°E), significant increases in summer extreme high temperature days (EHTDs) have already commenced since the mid-1990s, with the peaks centered on the surrounding areas of the Caspian Sea and Lake Baikal. Results indicate that compared with the period of 1960–1994 (P1), during 1995–2018 (P2) high-pressure and anticyclonic anomalies occupy the areas around the Caspian Sea and Lake Baikal, thus suppressing local cloud cover and precipitation, enhancing the solar radiation and high-temperature anomalies. The anticyclonic anomaly over Lake Baikal shows a close relationship with the increasing trend of global temperature, and the anomalous anticyclone over the Caspian Sea is under the influence of the warm North Atlantic and anomalous upper-troposphere jet stream during P2. The warmer than normal North Atlantic leads to the high-pressure anomaly over the Caspian Sea by modulating the Rossby wave activity. In addition, during P2, the temperatures in the middle North Atlantic and western Europe show greater increments than those over higher latitudes, and thus the temperature gradient enhances the westerly thermal wind, which therefore leads to an anomalous upper-level jet stream to the north of the Caspian Sea. Under this circumstance, the Caspian Sea is located to the right side of the anomalous jet exit, inducing the suppressed upward motion over there and favoring the occurrence of more EHTDs after the mid-1990s.